2015
DOI: 10.1152/ajpheart.00431.2015
|View full text |Cite
|
Sign up to set email alerts
|

Long-term physiological T3 supplementation in hypertensive heart disease in rats

Abstract: Animal studies suggest that hypertension leads to cardiac tissue hypothyroidism, a condition that can by itself lead to heart failure. We have previously shown that short-term thyroid hormone treatment in Spontaneously Hypertensive Heart Failure (SHHF) rats near heart failure is beneficial. This study tested the hypothesis that therapeutic, long-term T3 treatment in SHHF rats can prevent or attenuate cardiac dysfunction. Female SHHF rats were treated orally with a physiological T3 dose (0.04 μg/ml) from 12 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 25 publications
4
22
0
2
Order By: Relevance
“…65 TH treatment with both T3 and T4 is paralleled to a reduction of the interstitial fibrosis in animal models of ischaemic and non-ischaemic HF, and this effect may be related, at least in part, to the effect of TH on MMP and TIMP activity. 66,67 T3-dependent cardiac hypertrophy was not accompanied by interstitial fibrosis but an increase of MMP-2 and TIMP-2 expression was evidenced. 67 Similarly, in rats, cardiac hypertrophy induced by T3 treatment has been associated with an increase of MMP-1 activity, a reduction of collagen I and III and a decrease in TIMP-l and 4 expression.…”
Section: Thyroid System and Foetal Recapitulationmentioning
confidence: 91%
See 1 more Smart Citation
“…65 TH treatment with both T3 and T4 is paralleled to a reduction of the interstitial fibrosis in animal models of ischaemic and non-ischaemic HF, and this effect may be related, at least in part, to the effect of TH on MMP and TIMP activity. 66,67 T3-dependent cardiac hypertrophy was not accompanied by interstitial fibrosis but an increase of MMP-2 and TIMP-2 expression was evidenced. 67 Similarly, in rats, cardiac hypertrophy induced by T3 treatment has been associated with an increase of MMP-1 activity, a reduction of collagen I and III and a decrease in TIMP-l and 4 expression.…”
Section: Thyroid System and Foetal Recapitulationmentioning
confidence: 91%
“…71,72 T3 induced angiogenesis has been documented in several experimental rat models of cardiovascular disease, including ischaemia, hypertension and diabetic cardiomyopathy. 32,66,73 In a rat model of post-ischaemic HF, T3 supplementation to correct the low T3 state favoured a better retention of capillary density in the border zone in association with HIF-1 alpha stabilisation and TR alpha 1 upregulation. 72…”
Section: Thyroid System and Neo-angiogenesismentioning
confidence: 99%
“…Possible crosstalk between β-adrenergic signaling and T4-induced activation of MAPK could explain this overresponse in LNCaP cells; however, this relationship seems to be complex and is not yet clear. Clinical and experimental studies have shown that chronic systolic and/or diastolic hypertension, which are associated with a high mortality risk in prostate cancer, are also accompanied by lower levels of free T4 and T3 (2,73,74). Antagonistic T3 effects on β-adrenergic signaling are consistent with the notion that synergism is lost when one of these systems is enhanced or depressed; nevertheless, meticulous studies are needed to analyze if changes in the ratio of T4/T3 could be relevant for prostate cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…In cardiac fibroblasts, although TH increase the expression of TGF-β1, a pro-fibrotic marker, TH also promote a decrease in type 1 collagen gene expression, the major fibrillar collagen in the heart (54,55,56). In fact, different studies in the literature have shown that TH induce cardiac hypertrophy without increasing collagen deposition (57,58,59).…”
Section: Th In Cardiac Cellsmentioning
confidence: 99%